International trade and labour market integration of immigrants. (5th February 2022) - Lodefalk, Magnus; Sjöholm, Fredrik; Tang, Aili
Abstract: We examine whether international trade improves labour market integration of immigrants in Sweden. Immigrants participate substantially less than natives in the labour market. However, trading with a foreign country is expected to increase the demand for immigrants from that country. By hiring immigrants, a firm may access foreign knowledge and networks needed to overcome information frictions in trade. Using granular longitudinal matched employer–employee data and an instrumental variable approach, we estimate the causal effects of a firm's bilateral trade on employment and wages of immigrants from that country. We find a positive, yet heterogeneous, effect of trade on immigrant employment but no effect on immigrant wages.